(Oxalato)borate: The key ingredient for polyethylene oxide based composite electrolyte to achieve ultra-stable performance of high voltage solid-state LiNi0.8Co0.1Mn0.1O2/lithium metal battery. (February 2021) - Cheng, Samson Ho-Sum; Liu, Chen; Zhu, Fangyan; Zhao, Liang; Fan, Rong; Chung, Chi-Yuen; Tang, Jiaoning; Zeng, Xierong; He, Yan-Bing
Abstract: Searching novel polyethylene oxide (PEO) based composite electrolyte that can be compatible with high voltage cathodes (> 4 V) at room temperature is a long-standing challenge, but essential to achieve high-energy-density for solid-state lithium (Li) metal batteries. Herein, we develop an advanced dual-salts reinforced PEO/garnet solid-state composite electrolyte (SCE) with high ionic conductivity of 9 × 10 −4 S cm −1 and an electrochemical stability window up to ~ 4.7 V, where the lithium bis(oxalate)borate (LiBOB) is used as additive with LiClO4 . The dual-salts reinforced SCE can achieve excellent room temperature cycling performance of LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/Li metal batteries. The multiplied polymer-ion interactions and formation of Li‒B‒O/C‒O species originated from the (oxalato)borate group of LiBOB effectively promotes the electrochemical stability of the PEO based composite electrolyte and its wetting properties with electrodes. Unwanted non-conductive decomposition products, such as Li2 O and Li2 CO3, and NCM particles cracking during cycling are successfully suppressed. The NCM811 solid-state cells using the optimized dual-salts composite electrolyte delivers high specific capacity of 190 mA h g −1 and exhibit stable cycling performance for more than 200 cycles at 25 °C. Graphical Abstract: Stable charge–discharge performance of 4 V NCM solid-state battery are realized via addition of LiBOB salts to conventional single salt plasticized PEO solid-state composite electrolyte. Polymer electrolyte decomposition and active materials cracking at high voltage are suppressed by multiplied polymer-ion interactions and formation of stable C‒O/Li‒B‒O containing solid electrolyte interphase, leading to strikingly improvement in capacity retention. ga1 Highlights: A fast ion conducting dual-salts polyethylene oxide (PEO) based solid-state composite electrolyte (SCE) is developed. Electrochemical stability of the SCE is greatly enhanced via addition of lithium bis(oxalate)borate (LiBOB) salt. Adding LiBOB salt to the PEO-based SCE enables stable cycling of high voltage solid-state LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/Li battery.